Investigating the factors affecting self-care behaviors in diabetic patients: A systematic review - Leila Zarei (Journal of Biological Research, 2022)
Diabetes is one of the most common non-communicable diseases that have far-reaching economic and social consequences and threaten the national production and economy of countries. However, diabetes is a disease of self-control. Therefore, self-care strategies can maintain patients' independence while reducing the burden imposed on health care resources. This study aimed to investigate the factors affecting self-care behaviors in diabetic patients. This study is a systematic review; Google Scholar, SID, Scopus, PubMed, Science Direct, and ISI databases were used; 17,500 articles were found including the keywords "self-care", "diabetes" and "affecting factors" in the search process and all studies after 2010 were included. After reviewing the titles and abstracts, 51 studies were included. The studies' reports on self-care behaviors and their prevalence were very different depending on the tools used . The studies show the relationship between various factors including demographic, socio-economic, and psychological with self-care behaviors in patients with diabetes, which the most important variables included educational status, age, gender, marital status, BMI, occupational status, duration of illness, comorbidities, income, having glucometer, perceived severity of the disease and its complications, perceived barriers, diabetes distress, diabetes knowledge, perceived susceptibility, self-efficacy, social and family support, depression, anxiety. Due to the relationship of demographic, socio-economic, and psychological factors with self-care behaviors in patients with diabetes, it is suggested that a comprehensive program for the management of caring behaviors in diabetic patients should be designed to include all of the above.